Chemical composition of Enterococcus faecalis in biofilm cells initiated from different physiologic states - Liu, Hongyan; Xu, Qiong; Huo, Lijun; Wei, Xi; Ling, Junqi (Folia microbiologica, 2014)
Enterococcus faecalis is a ubiquitous bacterium of the gut that is observed in persistent periradicular infections. Its pathogenicity is associated with biofilm formation and the ability to survive under nutrient-poor (starvation) conditions. However, characteristics of chemical composition of biofilm cells developed by starved E. faecalis cells remain poorly understood. In this study, E. faecalis cells in exponential, stationary, and starvation phases were prepared and separately cultured to form biofilms. Confocal laser scanning microscopy was performed to verify biofilm formation. Raman microscopy was used to investigate the chemical composition of cells within the biofilms. Compared to cells in exponential or stationary phase, starved cells developed biofilms with fewer culturable cells (P < 0.05). Raman analysis revealed that cells produced in the biofilms from starved planktonic cells contained more protein and less nucleic acids than either the corresponding planktonic cells or the cells in biofilms from planktonic cells in exponential or stationary phases, suggesting that biofilm-grown cells from the starvation phase were characterized by increased synthesis of proteins and decreased nucleic acids. This study provides an insight into the chemical composition of biofilm cells developed by starved E. faecalis.
Keywords: nukleové kyseliny; Spectrum Analysis, Raman; Nucleic Acids; Biofilms; Proteins; Enterococcus faecalis; proteiny; Ramanova spektroskopie; biofilmy